Predation pressure in Ugandan cotton fields measured by a sentinel prey method. Issue 2 (10th January 2015) - Howe, Andy G.; Nachman, Gösta; Lövei, Gábor L.
Abstract Pest suppression by natural enemies is an important ecosystem service, which is a valuable resource to poor smallholders in developing countries. Diverse natural enemy assemblages of arthropod predators and parasitoids are documented in various regions in Africa, but our knowledge of their impact on herbivores in agroecosystems remains limited. We conducted experiments in cotton, Gossypium hirsutum L. (Malvaceae), under typical local agronomic practices in Uganda to assess levels of predation pressure ascribed to natural enemies. We measured predation rates on artificial caterpillars made of plasticine glued to cotton plants. Predation pressure on cotton fields varied between 1.96 and 4.1% per day, but was not significantly influenced by cotton treatments (insecticide/no insecticide, monocropping/intercropping with Phaseolus spp.). Predation pressure in non‐crop habitats adjacent to cotton fields was up to 12× higher than in the fields. Marks left on the artificial caterpillars revealed that arthropods and birds were largely accountable for predation in cotton fields, whereas arthropods and small mammals were dominant in non‐cultivated habitats.